EFFECTS OF SOME HERBAL PLANT EXTRACTS AGAINST PHARAOH ANT, Monomorium pharaonis (Linnaeus) - Tangchitphinitkan*, Phongpen; Visetson, Suraphon; Maketon, Monchan; Milne, Manthana (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2007)
This research was to evaluate the efficiency of three Thai herbs, i.e., tuba root (Derris elliptica Benth.), yam bean seeds (Pachyrhizus erosus L.) and tea seed cake (Camellia sp.) against adult worker of the Pharaoh ant (Monomorium pharaonis L.) The results showed that the tuba root extracts exhibited LC50 against adult worker ca. 0.22 % w/v whereas yam bean seed extracts showed LC50 against adult worker ca. 0.35 % w/v and tea seed cake extracts showed LC50 against adult worker ca. 0.55 % w/v after 24 hours exposure, respectively. Keywords: Monomorium pharaonis L., Derris elliptica Benth., Pachyrhizus erosus L., Camellia sp., toxicity Corresponding author: E-mail: phongpen@yahoo.com